Temporal constraints in the use of demonstratives in Iberian Spanish - Zulaica Hernández, Iker (Borealis – An International Journal of Hispanic Linguistics, 2012)
Natural linguistic data show that a close relationship exists among demonstratives and time in Spanish. Such connection appears to be of a pragmatic nature whereby linguistic expressions that encode or denote time license the use of demonstratives under certain conditions.The aforementioned connection time-demonstration occurs when speakers employ demonstratives to refer to objects within the textual world (i.e. discourse referents). In this paper I explore the temporal constraints that impose restrictions in the use of demonstratives in Spanish and argue in favor of characterizing the relationship time-demonstration as a discourse deixis phenomenon in close connection with time deixis. The co-referential link that gets established between the distal demonstrative and the temporal expression is formalized and a presuppositional characterization provided for the three demonstratives in their discourse-deictic use.